Trying to make it: the enterprises, gangs, and people of the American drug trade - Gundur, Rajeev Vishwanath (Cornell University Press, 2022)
Home -- The southern border -- Immigration court -- The Santa Fe Street bridge -- Business as usual -- Father and son -- La Carrucha -- Violence -- The street -- The oasis -- The gangs of the valley -- Adelita and Calista -- A fear of corners -- Connections -- The city by the lake -- Gangland -- The twins -- Logistics -- Conclusion: the business of the American drug trade -- Epilogue: trainspotting.